Ze studiów nad dziejami klasztoru Kanoników Regularnych na górze Ślęży - Domański, Grzegorz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
Fifteen years after my attempt at summing up the results of the historical, and above all archaeological research on Ślęża mountain (Domański 2002 ‒ research as of 2000) the time has come to make some minor corrections and important additions, mainly related to the early years of St. Augustine’s monastery in Ślęża, which from the 12th century to 1494 owned the majority of the massif, and after 1494 the entire mountain. The location of the monastery on Ślęża has been a matter of discussion since at least the 19th century. Written sources unambiguously speak of its location on the mountain. In 2000, I presented several purported stages of the monastery’s construction on top of the mountain. When, following new discoveries, the supposed location of the monastery changed, I put forward the hypothesis that there was a preliminary stage in the monastery’s construction (perhaps in cooperation with messengers from the parent monastery) when the materials were collected and the ground was prepared. Next, the monks arrived and almost immediately construction started. Completion (or discontinuation) of construction could have coincided with the monks’ flight in 1146 to Wrocław. On the basis of the scant archaeological material discovered in the monastery building, the conclusion should be drawn that no part of it was used. The suggested location of the monastery on the edge of the order’s property is an indication that looking after the terrain was not the main goal of the venture. The construction material, traces of the structure’s foundations, elements of stonemasonry and the Ślęża plaque all hint at construction having at least commenced, while it remains a mystery at which stage it was abandoned. Generally, the construction of the Ślęża monastery is associated with the “production” of granite sculptures of lions. More importantly, they were discovered beyond the Ślęża massif, but the majority of researchers attribute them to the monastery. I agree with most art historians that the objects date back to the 12th century. Bearing in mind that in Western and South-European architecture, similar sculptures were placed in pairs at the doors of magnificent buildings, as the bases of columns, the Ślęża lions (8) must have been planned as decoration of four imposing entrances. However, as a majority of them cannot be paired (they were dedicated to two sides of a gate), the number of the original statues must have been greater. The Ślęża lions share many features with similar statues from the St. Gallen abbey; bearing in mind the contacts of the founder (Palatine Peter Wlast), they could have been the prototypes for the Ślęża lions.